Autoeficácia materna em amamentar durante o primeiro ano pós-parto em uma coorte de nascimentos no Nordeste do Brasil - Brito, Samya Waleska Farias (2019)
The self-efficacy of breastfeeding consists in maternal confidence in their ability to breastfeed, given that individuals need to believe that they can develop healthy behaviors to accomplish the tasks necessary to meet the established health goals. The paper is structured in two sections, containing a literature review chapter divided into three topics, namely: global overview of breastfeeding, risk factors for early breastfeeding interruption and maternal self-efficacy in breastfeeding. In the second section is the original article, which aims to prospectively investigate maternal self-efficacy in breastfeeding and its relationship with the duration of breastfeeding over the first year postpartum in a birth cohort of a municipality in northeastern Brazil. This was a prospective cohort study that followed the mother-child pair from birth to 12 months of age. Data collection was performed from February 2017 to August 2018, in 4 moments, the first in the maternity hospital of Rio Largo / AL and, subsequently, in 3 home visits. During the visits, the Breastfeeding Self-Efficacy Scale-Short Form / BSES-SF was interviewed to all breastfeeding mothers. Independent variables were collected using structured and pre-coded forms. Descriptive statistics, chi-square tests, and multinomial logistic regression models were performed to explore the predictive effects of breastfeeding self-efficacy over the period. A total of 240 mothers were eligible in the study. Women had a high BSES-SF score, with mean and standard deviation at 3, 6, and 12 months postpartum corresponding to 55.68 ± 5.94; 54.77 ± 6.24; 53.80 ± 5.70, respectively. However, the percentage of those classified in the high self-efficacy category at three months decreased by half at 12 months, but when mothers had this classification at the first moment analyzed, they weaned less in later months. It was concluded that the woman who had self-efficacy in discharging breastfeeding at the first moment presented maintenance of breastfeeding twice as long as the following investigated periods, when compared to those with lower self-efficacy.